Phylogeography of Aplocheilus panchax in Indonesia, with special focus on the Bangka Island population (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mustikasari D, Nuryanto A, Suryaningsih S. 2022. Phylogeography of Aplocheilus panchax in Indonesia, with special focus on the Bangka Island population. Biodiversitas 23: 2035-2046. Previous studies divided Blue panchax, Aplocheilus panchax into three different clades, namely West (W), Central (C), and East (E) clades. Blue panchax populations from Indonesia belong to the Central and East clades. However, that study did not include blue panchax samples from pits with harsh conditions in Bangka Island, Indonesia. Therefore, this study aimed to assess the phylogeography of blue panchax in Indonesia with a special focus on the Bangka Island population using the cytochrome c oxidase 1 (COI) gene. The results showed that genetic distance within Bangka Island population was less than 2%, while genetic distances between Bangka population and other populations were ranged from 103.87% to 122.10%. There was also a clear genetic gap between the Bangka and other populations, with the minimum gap was 101.94%. Furthermore, the seventy-nine sequences analyzed resulted 28 haplotypes with genetic variability of 0.221 for nucleotide diversity (p), 0.923 for Haplotype diversity (Hd), 68.028 for Fu’s Fs-test, 2.00 (P < 0.02) for Fu and Li’s D-test, and 2.365 (P < 0.02) for Fu and Li’s F-test; and 1.927 for Tajima's D test (0.10 > P > 0.05). The Bangka population of Aplocheilus panchax established a distinct clade from the Western (W), Eastern (E), and Central (C) clades. Molecular data established that the population on Bangka Island is a novel clade for Indonesia and a global blue panchax phylogeographic.
Keywords: Abandoned tin mining pits, genetic distance, haplotype, killifish, new clade position